(untitled) (Tạp chí Y học Cộng đồng, 2026)
Background: Disease pattern analysis at district-level Traditional Medicine and Rehabilitation departments provides essential evidence for healthcare planning in the context of population ageing and the increasing burden of non-communicable diseases in Viet Nam. Objectives: To describe the disease pattern and its changes among patients treated at the Department of Traditional Medicine and Rehabilitation, Cam Khe District Medical Center, Phu Tho Province, from 2022 to 2024. Methods: A retrospective cross-sectional descriptive study was conducted using all eligible medical records of patients receiving examination and treatment at the department between January 1, 2022 and December 31, 2024. Diagnoses were coded according to the International Classification of Diseases, 10th Revision (ICD-10). Demographic characteristics and disease groups were analyzed using descriptive statistics. Results: A total of 7,701 patient visits were included. Female patients, individuals aged 60 years and older, and manual workers accounted for the majority of cases. Non-communicable diseases predominated throughout the study period, representing over 98% of all cases annually. According to ICD-10 classification, diseases of the musculoskeletal system and connective tissue (Chapter XIII) were dominant in all three years, followed by diseases of the nervous system (Chapter VI) and diseases of the circulatory system (Chapter IX). Sciatica and low back pain showed an increasing trend and ranked among the most common conditions in later years. Conclusions: From 2022 to 2024, the disease pattern at the Department of Traditional Medicine and Rehabilitation, Cam Khe District Medical Center was characterized by a predominance of chronic non-communicable diseases, particularly musculoskeletal disorders, with notable changes in the ranking of common conditions over time.